2009
DOI: 10.1177/193672440900300202
|View full text |Cite
|
Sign up to set email alerts
|

Cleaning up after the Mess: The Individual-Community Nexus in Correctional Rehabilitation

Abstract: The population of America's local, state, and federal prisons increased by nearly 340 percent between 1980 and 2005 (Paparozzi and Demichele 2008). Much of this increase reflects policy intended to get tough on criminals by locking them up longer and removing discretionary power of judges. Therefore, community corrections (i.e., probation and parole) have assumed increased attention recently as more prisoners are diverted and placed on probation and others are released through mandatory parole. One of the most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Today, there is a widespread and unacceptable degree of relapse in violence after completion of violence treatment. In addition, Guy (2009) highlights the importance of learning-based therapy occurring in a nonthreatening environment in which the client/offender has the opportunity to reinforce new behaviors. If the theoretical premises used in this paper are true, other therapy models can be examined and further development of the therapy considered.…”
Section: Discussionmentioning
confidence: 99%
“…Today, there is a widespread and unacceptable degree of relapse in violence after completion of violence treatment. In addition, Guy (2009) highlights the importance of learning-based therapy occurring in a nonthreatening environment in which the client/offender has the opportunity to reinforce new behaviors. If the theoretical premises used in this paper are true, other therapy models can be examined and further development of the therapy considered.…”
Section: Discussionmentioning
confidence: 99%
“…Studies show participants enjoy the new skills they gain, develop a stronger work ethic, and hope to gain meaningful employment upon release (Christie et al 2016; DelSesto 2022; Moore, Freer, and Samuel 2015). Employment directly correlates with recidivism rates, with offenders being less likely to reoffend if they maintain a stable job (Guy 2009). Self-published recidivism rates of graduates of green prison programs are as low as 4 percent (e.g., Growing Gardens 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Ascencio (2018) showed that prison horticulture programs can provide prisoners with feelings of increased self-efficacy, success, and hope by learning new skills. These gardening attributes help teach the women prosocial attitudes rather than procriminal (Guy 2009).…”
Section: Benefits Of Gardens In Correctional Environmentsmentioning
confidence: 99%
See 2 more Smart Citations